Modelling and Dosimetry for Alpha-Particle Therapy - Sgouros, George (Curr Radiopharm, 2011)
As a consequence of the high potency and short range of alpha-particles, radiopharmaceutical therapy with alpha-particle emitting radionuclides is a promising treatment approach that is under active pre-clinical and clinical investigation. To understand and predict the biological effects of alpha-particle radiopharmaceuticals, dosimetry is required at the micro or multi-cellular scale level. At such a scale, highly non-uniform irradiation of the target volume may be expected and the utility of a single absorbed dose value to predict biological effects comes into question. It is not currently possible to measure the pharmacokinetic input required for micro scale dosimetry in humans. Accordingly, pre-clinical studies are required to provide the pharmacokinetic data for dosimetry calculations. The translation of animal data to the human requires a pharmacokinetic model that links macro- and micro-scale pharmacokinetics thereby enabling the extrapolation of micro-scale kinetics from macroscopic measurements. These considerations along with a discussion of the appropriate physical quantity and related units for alpha-particle radiopharmaceutical therapy are examined in this review.